Studies on essential oils of cinnamomum spp. from Sarawak - Dayang Monira, Jaya. (Universiti Malaysia Sarawak (UNIMAS), 2005)
Essential oil from the bark, leaf and root of three Cinnamomum species (c. zeylanicum, C. rhyncophyllum and C. iners) were extmcted using hydro distillation method and subsequently analysed using gas chromatography-flame ionization detector (GCIFID) and gas chromatography-mass spectrometry (GCIMS). Kovat indices for individual component in the essential oil were determined and these indices were used for identification to complement mass spectral data obtained from GCIMS analysis. The percentage yield of the essential oil ranged between 0.1-3.6 % and bark of C. rhyncophyllum gave the highest yield percentage of essential oil. Major component in the bark and the root of C. zeylanicum were methyl eugenol and methyl cinnamate, while the leaf contains linalool as its major component. The major components in the bark oil of C. rhyncophyllum were methyl eugenol and methyl cinnamate, while the major component of the leaf oil was linalool. The root of C. iners contains camphor and 1,8-cineole as its major components. Toxicity test conducted on all essential oils revealed that the root oil of C. zeylanicum posses the highest toxicity against brine shrimp, with LCso value of 27.5 llg/mL.